Ewolucja zakresu ochrony w grupowych ubezpieczeniach na życie w Polsce - Łyskawa, Krzysztof (Evolution of the protective function of group life insurance in Poland, 2006)
Until 1991, group life insurance in Poland could encompass employees and potentially their family members. However, the basic purpose of insurance stemmed from historic experience in such insurance claims which in most cases resulted in additional benefits due to unforeseeable life events such as death of employees or their family members. The appearance of foreign insurance companies on the Polish market led to the creation of life insurance policies with capital funds. This type of policy has enabled amalgamation of the protective function of insurance with the investment function. Over time however, it has been observed that the protective function played by insurance is limited due to certain insurance-holder habits as well as budget restrictions of potential insurance-holders.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 294-303